METODE PENAFSIRAN IBN KATHîR DALAM TAFSîR AL-QUR’âN AL-'AZIM - Aruf, Thohir (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2011)
When the Koran was revealed, the Prophet Muhammad serves as mubayyin, explained to his companions about the meaning and content of the verses of the Koran, particularly concerning the verses that are not understood or vague meaning. After the Prophet?s death, the friends do ijtihâd in understanding the verses of the Koran to address new issues that arise, especially those who have the ability like ?Alî b. Abî Tâlib, Ibn ?Abbâs, Ubay b. Ka?b and Ibn Mas?ûd. it is understood that the Tafsîr Ibn Kathîr is one interpretation, which, when viewed in terms of its interpretation is the interpretation of analytical methods decompose (tahlîlî). Meanwhile, when the terms of the sources of interpretation, it is a bi al-ma?thûr interpretation. But unlike other interpretations, in this interpretation the author has made criticism of the assessment of transmitters of hadith or athar friends, and have downloaded the Legal Affairs Committee (reinforce) opinion one of several different opinions, so this interpretation when viewed from a history that is mentioned more accounted